Efficient Perovskite Indoor Photovoltaics with Open‐Circuit Voltage of 1.15 V via Collaborative Optimization of CsPbI2Br Layer and Hole Transport Layer. Issue 10 (28th August 2022) - Jiang, Shan; Bai, Yinglong; Xu, Zhiyang; Wang, Fuzhi; Xia, Lixing; Yang, Yun; Li, Chenghao; Tan, Zhan'ao
Abstract: All‐inorganic CsPbI2 Br perovskite has attracted great attention due to the stable crystal structure and moisture resistance, and its 1.91 eV bandgap is close to the optimal bandgap of indoor artificial light sources, making it be the best candidate for the indoor photovoltaics (IPVs) to power a wide range of internet of things related electronic devices. Herein, we report on the preparation of CsPbI2 Br with α‐phase and the improvement of its phase stability by adding lead acetate in the CsPbI2 Br precursor. A series of dopant‐free conjugated polymers (P3HT, PBDB‐T, and PM6) with different highest occupied molecular orbital energy levels are introduced as hole transport layers for building IPV devices. The PM6 based devices having better energy alignment with perovskite demonstrate best indoor photovoltaic performance, giving a remarkable open‐circuit voltage of 1.15 V and high fill factor of 81.86% under 1000 lux (330 µW cm −2 ) light‐emitting diode illumination, and finally realizing a decent power conversion efficiency of 33.68%. Our findings suggest that collaboratively optimize the CsPbI2 Br layer and hole transport layer is an effective approach to realize high performance IPVs. Abstract : Lead acetate is introduced into the precursor to improve the α‐phase stability of CsPbI2 Br, and the dopant‐free PM6 is employed as hole transport layer to further optimize the charge transport, which collaboratively contribute to a power conversion efficiency of 33.68% for the indoor photovoltaic cell, along with a remarkable open‐circuit voltage of 1.15 V, testing under a 1000 lux light‐emitting diode illumination.